EDUKASI BERBASIS DARING BAGI SISWA SEKOLAH DASAR PADA MASA PANDEMI COVID-19 DI DESA PASIR LOR, KECAMATAN KARANGLEWAS, KABUPATEN BANYUMAS - Kharisma Linda Fajriyani; Nur Azizah (LPPM STAIMAS WONOGIRI, 2021)
The Covid-19 pandemic has taken a toll on many people. What was initially detrimental in the economic field has now spread to the education sector. Online learning has been carried out since the Covid-19 pandemic. For now, learning activities are required to use online-based educational methods so as not to cause crowds that can lead to an increase in Covid-19 cases. Many parents and children complain about online learning methods. This method is considered less effective because students are less able to understand the material presented by the teacher. Lack of maximum preparation in terms of field readiness. Therefore, the author wants to research online-based education for elementary school students during the Covid-19 pandemic in Pasir Lor Village, Karanglewas District, Banyumas Regency. However, researchers are more focused on RT.02 RW.02 only. The result is that elementary school students still need assistance in online learning to understand the subject matter, so they need learning media support and parental support so that elementary school students are able to follow online learning well.